2012
DOI: 10.1021/ja302970x
|View full text |Cite
|
Sign up to set email alerts
|

Attach, Remove, or Replace: Reversible Surface Functionalization Using Thiol–Quinone Methide Photoclick Chemistry

Abstract: A very facile reaction between photochemically generated o-naphthoquinone methides (oNQMs) and thiols is employed for reversible light-directed surface derivatization and patterning. A thiol-functionalized glass slide is covered with an aqueous solution of a substrate conjugated to 3-(hydroxymethyl)-2-naphthol (NQMP). Subsequent irradiation via shadow mask results in the efficient conversion of NQMP into reactive oNQM species in the exposed areas. The latter react with thiol groups on the surface, producing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
86
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 53 publications
0
86
0
5
Order By: Relevance
“…Popik et al [18] showed that reactive o-naphthoquinone methides (oNQMs) produced under UV light from 3-(hydroxymethyl)-2-naphtholcould react with surface thiol groups to yield thioether conjugates, which could be subsequently cleaved by a secondary UV irradiation to regenerate surface thiol groups. [18] In a recent publication, Anseth et al described the use of allyl sulfides incorporated into a hydrogel to achieve reversible modification with thiol-containing biomolecules. [19] Here, we present a new reversible photo-patterning strategy based on a photo-induced disulfide exchange reaction that allows for reversible photo-functionalization, patterning, as well as exchange or removal of surface functional groups (Figure 1).…”
mentioning
confidence: 99%
“…Popik et al [18] showed that reactive o-naphthoquinone methides (oNQMs) produced under UV light from 3-(hydroxymethyl)-2-naphtholcould react with surface thiol groups to yield thioether conjugates, which could be subsequently cleaved by a secondary UV irradiation to regenerate surface thiol groups. [18] In a recent publication, Anseth et al described the use of allyl sulfides incorporated into a hydrogel to achieve reversible modification with thiol-containing biomolecules. [19] Here, we present a new reversible photo-patterning strategy based on a photo-induced disulfide exchange reaction that allows for reversible photo-functionalization, patterning, as well as exchange or removal of surface functional groups (Figure 1).…”
mentioning
confidence: 99%
“…QMs represent a readily available class of electrophiles capable of both capture and release of various nucleophiles 34 . These species are typically formed only transiently, and yet have found utility in the synthesis of natural products 35,36 , polymers 37 and cytotoxic agents 38 , as well as in functionalization of molecular surfaces 39 . QM formation and regeneration are exquisitely sensitive to electronic effects as evident from the five orders of magnitude separating rate constants for QMs differing by a single substituent 31,40 .…”
mentioning
confidence: 99%
“…Functional surfaces were obtained by reacting the liberated thiol with maleimides or isocyanates. An interesting contribution from Popik and co-workers [144] describes a different approach for surface photoderivatization, based on the use of onaphthoquinone methides (oNQM). The thioether linkage created by reaction of thiol and oNQM is stable under ambient conditions but can be cleaved by UV-irradiation, regenerating the free thiol.…”
Section: Photosensitive Protection Groupsmentioning
confidence: 99%